Risk Level Measurement of Integrated Broadband Village Program in Papua and East Nusa Tenggara Region (Pengukuran Tingkat Risiko Program Desa Broadband Terpadu di Wilayah Papua dan Nusa Tenggara Timur) - Mukhlis Amin (BBPSDMP KOMINFO MAKASSAR, 2017)
This study is measuring the risk level of the sustainability program of Integrated Rural Broadband and risk mitigation planning. Observations on the operation of each component of the system such as infrastructure, information networks, services and applications, readiness support facilities, human resources and regulatory is focused by studying the level of risk that can lead to the failure of the program. Measurement of the level of risk is carried by the semi-quantitative method. The data used is the research data about Risk Management Program of Integrated Rural Broadband in Indonesia especially in Papua and East Nusa Tenggara. The measurement results have shown low risk category for four villages, the remain are at medium and high risk categories. The highest risk category is the category of Human Resources, Information Network and Support Facilities. To maintain the continuity of DBT has been built, it is recommended to do risk management based on the causes of risk which has been identified.Penelitian ini melakukan pengukuran tingkat risiko keberlangsungan program Desa Broadband Terpadu (DBT) serta perencanaan mitigasi risikonya.Pengamatan pada tiap komponen sistem penyelenggaraan seperti infrastruktur, jaringaninformasi, layanan dan aplikasi, kesiapan fasilitas pendukung, sumber daya manusia serta regulasidifokuskan dengan mempelajari tingkat risiko yang dapat bermuara pada kegagalan program. Pengukuran tingkat risiko dilakukan dengan metode semikuantitatif. Data yang digunakan adalah data hasil penelitian tentang Penanganan Risiko Program Desa Broadband Terpadu di Indonesia khususnya di wilayah Papua dan Nusa Tenggara Timur.Hasil pengukuran menunjukkan empat desa yang termasuk dalam kategori risiko rendah, selebihnya termasuk kategori risiko sedang dan tinggi. Kategori risiko yang paling tinggi adalah kategori Sumber Daya Manusia, Jaringan Informasi dan Fasilitas Pendukung. Untuk menjaga keberlangsungan DBT yang telah dibangun maka direkomendasikan penanganan risiko berdasarkan penyebab risiko yang telah diidentifikasi.